Stability analysis of the D-dimensional nonlinear Schrodinger equation with trap and two- and three-body interactions - Gammal, A.; Frederico, T.; Tomio, L.; Abdullaev, F. K. (Elsevier B.V., 2000)
Considering the static solutions of the D-dimensional nonlinear Schrodinger equation with trap and attractive two-body interactions, the existence of stable solutions is limited to a maximum critical number of particles, when D greater than or equal to 2. In case D = 2, we compare the variational approach with the exact numerical calculations. We show that, the addition of a positive three-body interaction allows stable solutions beyond the critical number. In this case, we also introduce a dynamical analysis of the conditions for the collapse. (C) 2000 Published by Elsevier B.V. B.V. All rights reserved.
Keywords: nonlinear Schrodinger equation; trapped two and three-body atomic systems; multidimensional systems